2008
DOI: 10.1097/bpo.0b013e318164ee2d
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Occult Dysplasia of the Contralateral Hip in Children With Unilateral Hip Dysplasia

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…Although the left hip is typically more involved in those with unilateral dysplasia, there is significant ethnic variability, 44% in Indo-Mediterraneans to 81.4% in Caucasians from Australia/New Zealand (Figure 3(c)). The prevalence of mild adult acetabular dysplasia in children with documented unilateral DDH is up to 40% [233]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the left hip is typically more involved in those with unilateral dysplasia, there is significant ethnic variability, 44% in Indo-Mediterraneans to 81.4% in Caucasians from Australia/New Zealand (Figure 3(c)). The prevalence of mild adult acetabular dysplasia in children with documented unilateral DDH is up to 40% [233]. …”
Section: Resultsmentioning
confidence: 99%
“…The opposite hip in “unilateral DDH” children often develops abnormally: 14% [460], 31% [461], 34% [462], and 43% [233]. The center-edge angle is the most predictive single measurement of delayed acetabular development while the overall best predictor is the hip ratio (CE angle + 100(acetabular depth/acetabular diameter))/2 [461].…”
Section: Resultsmentioning
confidence: 99%
“…Another study evaluated children with unilateral hip dysplasia for a contralateral hip dysplasia that was not apparent with thorough and recurring evaluations early in childhood. The authors showed that mild dysplasia of the hip can develop as the child grows older [175] . This emphasizes the significance of thorough and recurring clinical and radiographic examinations.…”
Section: Follow-upmentioning
confidence: 99%
“…The author (David et al, 2015) in their study found a 4% recurrent dysplasia after successful treatment of DDH so they recommended follow-up to 6 month of infant age. (Song et al, 2008) reported that the hipdysplasia of mild severity could develop as the child grows older even with successful treatment by Pavlik harness.…”
Section: Resultsmentioning
confidence: 99%